ANALISIS STRATEGI PERANCANGAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI MENGGUNAKAN TOGAF ADM (STUDI KA-SUS: TK TUNAS BANGSA SMART) - Yunita, Selviana; Haspianto, Mauli (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2024)
Kindergarten (TK) is a formal educational institution for early children in Indonesia. Kindergartens provide preschool education for children before entering Primary School. Information technology has a significant impact on several aspects of educational institutions, such as learning systems, school management, administrative systems, and policy planning. By using information technology, schools want to improve the quality of the educational offer. Tunas Bangsa Smart is one of the kindergartens that want to improve the quality of their education. This study seeks to establish TOGAF ADM as an enterprise architecture model for information systems, specifically designed to support operations in TK Tunas Bangsa smart. The purpose of this study is to produce blueprints of enterprise Architecture Design at TK Tunas Bangsa Smart using TOGAF ADM method. The Open Group Architecture Framework (TOGAF) is a comprehensive framework designed specifically for enterprise architecture development. Based on the results of research that has been conducted on the design of Information Systems in kindergartens, an overview of Information System Design models that suit user needs can be obtained. Value chain analysis produces 2 activities, namely the main activity and supporting activities which can produce application proposals are generated that are expected to improve existing business processes.